Green Citizens: Environmental Education by the Media and Environmental Non-Governmental Organisations (ENGOs) in Malaysia - Mohamad Saleh, Mohamad Saifudin; Balaraman, Rani Ann; Syed Mukhiar, Sharifah Nadiah (2017)
Media and environmental non-governmental organisations (ENGOs) have been recognised as two most active and indispensable stakeholders in supporting environmental education in Malaysia. Environmental education by both media and ENGOs is undoubtedly crucial in producing more ―green‖ citizenship that is well equipped with environmental knowledge and has a great attitude and practices on preserving and conserving the environment. This paper sought to discuss on how the Malaysian media, particularly The Star and Utusan Malaysia and the Malaysian ENGOs particularly World Wide Fund for Nature (WWF) Malaysia and Malaysia Nature Society (MNS) plays their vital roles in environmental education and the challenges faced by them in educating public about the environment. For the purpose of this study, a total of 24 interviewees encompassing 13 interviewees from Utusan Malaysia and The Star and 11 interviewees from WWF Malaysia and MNS were interviewed. The findings from interviews confirmed that both the Malaysian media and ENGOs have shared quite a similar role in environmental education, particularly in delivering environmental awareness and knowledge to public. However, the media is more focusing on educating the public about environment through their feature and news articles published on newspapers while the ENGOs‘ environmental education are not only via their newsletters but also through environmental programs like eco-school and eco-institute conducted by WWF Malaysia and School Nature Club (KPA) and KPA for youth conducted by MNS. In fact, unlike the media, the Malaysian ENGOs have more privileges as they have specific education teams that specifically handle environmental education in a more thorough and structured way. Both media and ENGOs interviewees from this study concluded that the main challenges of environmental education in Malaysia are the environmental topic itself that is too technical, dry and boring, despite of other challenges like the Malaysian public‘s low knowledge on environment.